Experimental measurements of propulsive factors in regular deep-water following waves for a fishing trawler. (1st November 2022) - Saettone, Simone; Lopez-Olocco, Tomas; Medina-Manuel, Antonio; Taskar, Bhushan; Steen, Sverre; Andersen, Poul
Abstract: The results of load-varying self-propulsion model-scale experiments in calm water and regular deep-water following regular waves are presented. Open water tests were also performed at different propeller rotational speeds to evaluate the impact of the Reynolds number on the propeller thrust and torque. A model-scale fishing trawler was selected as the case study. Two ship speeds were considered. The open water curves showed a minimal influence of the Reynolds number on the thrust coefficient. However, the torque coefficient decreased with the increase of the Reynolds number. A good linear relationship between the tow force and the propeller thrust was detected in following waves and calm water conditions. The effective wake fraction increased in following waves compared to calm water conditions. The amplitude of the effective wake fraction decreased with the increase of the ship speed. A small influence of the ship motions and wave–particle velocities was reported on the thrust deduction fraction. The hull, relative rotative, propeller, and propulsive efficiency increased compared to calm water. The propulsive characteristics were estimated by considering the wave added resistance and the propulsive coefficients equal to their calm water values. Compared to the propulsive characteristics computed with the propulsive coefficients measured in waves, the propulsive efficiency was underestimated by about 2%–5%. Highlights: The effective wake fraction increased in following waves compared to calm water. The amplitude of the effective wake fraction decreased with the increase of the ship speed. The ship motions and wave–particle velocities had a small influence on the thrust deduction fraction. The hull, propeller, and propulsive efficiency increased compared to calm water. The propulsive efficiency determined by considering only the wave added resistance was underestimated by about 2%–5%.